Injustiça ambiental em áreas de risco a desastres no município de São José dos Campos - Barbarotto Junior, Jorge Luiz [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The geographic space occupation can occur through different logics in the forms of intervention and society occupation. These can be conduct by different interests, sometimes related to conflicts streaky in society. In terms of unequal occupations of the geographic space, the theme of this work is the configuration of environmental injustice conditions in certain forms of land use, leading in many cases to the establishment of risk areas, occupied mainly by the most vulnerable populations. Thus, the general objective of the work is defined as an evaluation from the perspective of the concept of environmental injustice applied at disasters risk areas. The methodological proposal of this study was based first on the elaboration of bibliographic review that brings together themes that converge assessment environmental injustice conditions for disaster risk areas. Therefore, the following topics were addressed: political ecology, environmental justice, risk areas concepts, relief as a resource, disasters, vulnerability, hazards, resilience, and laws applied to disasters. Subsequently, as a system of verifying a possible way of operationalizing these concepts, a case study was developed to evaluate the risk areas condition in São José dos Campos. The study case was developed first with the physical and socioeconomic characterization for the whole municipality in general, then the specific characterization for the risk areas was carried out through detailed data for these areas, highlighting the data from the mapping carried out by IPPLAN (2016) and SEADE (2013). Thus, the study case was concluded with a summary of the risk areas in relation to the municipality and possible associations with the environmental injustice concept. At the end, through the topics covered and the study case developed, it was noted that the municipality of São José dos Campos, despite having good percentage rates of social vulnerability in relation to the State, when compared with the rates of its population in risk areas, the same demonstrates that there is a tendency to direct the occupation of the most susceptible areas, with geomorphologies more prone to landslides, mainly in the peri-urban regions to the north and south of the city, by populations of medium or high vulnerability.

A ocupação do espaço geográfico pode ocorrer por diferentes lógicas nas formas de intervenção e ocupação da sociedade. Estas podem ser regidas por diferentes interesses por vezes relacionadas aos conflitos entremeados na sociedade. Dentro de um contexto de ocupações desiguais do espaço geográfico, o tema deste trabalho é a configuração de condições de injustiça ambiental em determinadas formas de ocupação do relevo, levando em muitos casos ao estabelecimento de áreas de risco, ocupadas principalmente pelas populações mais vulneráveis. Assim, o objetivo geral do trabalho é definido como a avaliação da perspectiva do conceito de injustiça ambiental aplicado em áreas de risco a desastres. A proposta metodológica para o desenvolvimento do estudo pautou-se primeiramente na elaboração de uma revisão bibliográfica que reúne conceitos que convergem para a avaliação de condições de injustiça ambiental em áreas de risco a desastres. Assim, foram abordados os seguintes conceitos: ecologia política, justiça ambiental, áreas de risco, o relevo como recurso, desastres, riscos, vulnerabilidade, perigo, resiliência e legislação aplicada a desastres. Posteriormente, como forma de verificar a operacionalização destes conceitos, foi desenvolvido um estudo de caso para avaliar a condição das áreas de risco no município de São José dos Campos - SP. O estudo de caso se desenvolveu primeiramente com a caracterização física e socioeconômica para todo município, em seguida realizou-se a caracterização específica para as áreas de risco por meio de dados detalhados para estas áreas, destacando-se os dados do mapeamento realizado pelo IPPLAN (2016) e a base de dados IPVS (SEADE, 2013). O estudo de caso foi concluído com uma síntese das áreas de risco em relação ao município e possíveis associações com o conceito de injustiça ambiental. Ao final do trabalho notou-se que o município de São José dos Campos, apesar de apresentar bons índices percentuais de vulnerabilidade social em relação ao estado de São Paulo, quando comparado com os índices de sua população em área de risco verifica-se uma tendência em direcionar a ocupação das áreas mais suscetíveis, com formas de relevo mais propensas a movimentos de massa, principalmente nas regiões periurbanas ao norte e ao sul da cidade, pelas populações de vulnerabilidade média ou alta.
Environmental injustice in disaster risk areas in the municipality of São José dos Campos
Keywords: Environmental justice; Risk area; Relief; Geomorphology; Justiça ambiental; Áreas de risco; Relevo; Geomorfologia